Policy risks to the fiscal outlook - Carl Emmerson; Martin Mikloés; Isabel Stockton (Institute for Fiscal Studies (IFS), 2023)
Pressures on both revenue and spending are skewed to add to borrowing over the next few years, and threaten the "centrality" of official forecasts.
Keywords: 330; Government finances and spending; Taxes and benefits; IFS Green Budget 2023; Government spending